Göteborg municipality: Personnel November 1991 - Göteborgs kommun (City of Gothenburg, 1996)
This datasets includes information on sex, age, position, personnel category, full-time, part-time or hourly-paid employment, for all persons employed by the Göteborg municipality in March 1989, November 1991, and November 1993.

This datasets includes information on sex, age, position, personnel category, full-time, part-time or hourly-paid employment, for all persons employed by the Göteborg municipality in March 1989, November 1991, and November 1993.
Göteborgs kommun: Personalstatistik november 1991
Keywords: occupations; yrken; employment; anställning; Employment; Sysselsättning; Government, political systems and organisations; Regering, politiska system och organisationer; Social Sciences; Samhällsvetenskap; Sociology; Sociologi